1973
DOI: 10.1302/0301-620x.55b3.595
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cortisone and Implantation Site on Bone and Cartilage Induction in Various Animals

Abstract: 1. Decalcified lyophilised rat bone matrix prepared by Urist's method acts as an inductor of cartilage and bone when implanted into animals of other species, namely mice, rabbits and gerbils. Induction in rabbits and gerbils was very much weaker than in the mouse. 2. The site of implantation affected the outcome; intramuscular implants induced cartilage and bone more strongly and regularly than subcutaneous or intraperitoneal implants. 3. Rabbit transitional epithelium, growing in cortisone-treated gerbils, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The phenomenon of bone induction by implantation of transitional epithelium is not species-specific; dogs [1], guinea pigs [2] and cats [3] are good responders to both auto-and allogenic grafts, while in rats [4], gerbils [5], rab bits [5] and hamsters [6] the incidence and yield of induced bone by allogeneic uroepithelium are low [for and female patients at the Urology Clinic of the Medical Academy of Warsaw suffering from urothelial or kidney carcinoma. No informed consent was requested because the material was discarded during routine surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of bone induction by implantation of transitional epithelium is not species-specific; dogs [1], guinea pigs [2] and cats [3] are good responders to both auto-and allogenic grafts, while in rats [4], gerbils [5], rab bits [5] and hamsters [6] the incidence and yield of induced bone by allogeneic uroepithelium are low [for and female patients at the Urology Clinic of the Medical Academy of Warsaw suffering from urothelial or kidney carcinoma. No informed consent was requested because the material was discarded during routine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical reports pointing to the link between surgical injury of human uri nary bladder and the appearance of bone tissue in the adjacent muscles have suggested that human transitional epithelium possesses osteoinductive potency [15,16]. An attempt to show the osteoinductive property of human urinary bladder mucosa grafted into the anterior chamber of the guinea pig eye (a site considered immunoprotective) gave negative results and the lack of bone induction was explained by the histoimcompatibility reaction that destroys grafted epithelium [14], The application of im munosuppression by cortisone opened the possibility of prolonging xenogeneic epithelium survival long enough to reveal its osteoinductive properties [11], In mice corti sone does not inhibit heterotopic osteogenesis by epithe lial cells or by bone morphogenetic protein [5,7,8,11]. Therefore, we used this approach to examine whether human transitional epithelium belongs to the group of bone-inducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…In nine implants prepared from four cases (noninvasive papillary transitional-cell carcinoma of the bladder and invasive papillary transitionalcell carcinoma of the bladder, two cases each) a small amount of cartilage and/or bone was found in the stroma of grafted tissue. The rarity of this phenomenon -together with the observation that implants of normal human urinary-tract mucosa have never induced the formation of cartilage/bone, whereas in a similar system, dog or guineapig grafts are osteogenic -suggests that the cartilage/bone present in the stroma of implanted cancers is the result of metaplasia of the stroma of the neoplasm and not the product of any osteoinductive potency of human urothelium.Heterotopic osteogenesis following urinary-tract mucosa implantation is a phenomen observed in many species, such as dogs, cats, rabbits, gerbils, and guinea pigs, but the osteogenic potential varies among species [ 1,11,21 ]. Some species, such as mice and rats, respond well to xenogeneic transitional epithelial transplants, whereas on transplantation into auto-or allogeneic systems, their own Correspondence to: K. H. W{odarski urinary-tract epithelia only occasionally induce bone formation [3, 20].…”
mentioning
confidence: 99%
“…Heterotopic osteogenesis following urinary-tract mucosa implantation is a phenomen observed in many species, such as dogs, cats, rabbits, gerbils, and guinea pigs, but the osteogenic potential varies among species [ 1,11,21 ]. Some species, such as mice and rats, respond well to xenogeneic transitional epithelial transplants, whereas on transplantation into auto-or allogeneic systems, their own Correspondence to: K. H. W{odarski urinary-tract epithelia only occasionally induce bone formation [3,20].…”
mentioning
confidence: 99%